Comparison between l-CHOP and an l-CHOP protocol with interposed treatments of CCNU and MOPP (l-CHOP-CCNU-MOPP) for lymphoma in dogs - Rassnick, K. M.; Bailey, D. B.; Malone, E. K.; Intile, J. L.; Kiselow, M. A.; Flory, A. B.; Barlow, L. L.; Balkman, C. E.; Barnard, S. M.; Waite, A. H. (Veterinary & comparative oncology, 2010)
An l‐CHOP protocol with interposed treatments of CCNU and MOPP (l‐CHOP‐CCNU‐MOPP) was evaluated in 66 dogs with stages III–V lymphoma. Results were compared with a historical group of 71 dogs treated with an l‐CHOP protocol. Complete remission (CR) rates (85 and 80%, respectively) did not differ significantly between protocols (P = 0.48). First CR duration for dogs treated with l‐CHOP‐CCNU‐MOPP was significantly longer: median, 317 days; 2‐year CR rate, 35% versus median, 298 days; 2‐year CR rate, 13%, P = 0.05). For the l‐CHOP‐CCNU‐MOPP protocol, dogs in substage‐b had a 4.3 times greater hazard of having a relapse than dogs in substage‐a (P = 0.002). Frequency of adverse chemotherapy‐associated gastrointestinal effects did not differ between protocols (P = 0.77). Neutropenia (primarily after CCNU) occurred more frequently in dogs treated with l‐CHOP‐CCNU‐MOPP (P < 0.001). In summary, the l‐CHOP‐CCNU‐MOPP protocol showed an improved duration of first CR as compared with an l‐CHOP protocol, but the relevance of this finding might be subject to clinical judgement.